Could Partipative Decision Making Be Solution For Organizational Silence Problem? - Mehtap Sarıkaya; Sabahat Bayrak Kök (European Scientific Journal, ESJ, 2016)
Whereas participative decision making is considered as sharing decision making process with subordinates, organizational silence is unwillingness of employees to share their thoughts, interests and affections about organizational issues or problems and keeping them unexposed. The present study aims to explore the relationship between participative decision making and acquiescent silence, defensive silence and prosocial silence. Established hypotheses along the purpose of the present study were tested by means of correlation and regression analyses. Based on the analysis results, it was determined that participation in decision making process has negative influence on organizational silence, acquiescent silence and defensive silence.